2021
DOI: 10.1101/2021.08.19.456945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Harbor porpoise losing its edges: genetic time series suggests a rapid population decline in Iberian waters over the last 30 years

Abstract: Impact of climate changes on species is expected to be especially visible at the extremities of the species distribution, where they meet sub-optimal conditions. In Mauritania and Iberia, two genetically isolated populations of harbor porpoises form a distinct ecotype and are presumably locally adapted to the upwelling waters. By analyzing the evolution of mitochondrial genetic variation in the Iberian population between two temporal cohorts (1990-2002 vs. 2012-2015), we report a dramatic decrease in genetic d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Such relationship has also been reported in empirical studies (e.g. 37 , 38 ). We chose east coast Australia because of documented reductions in tiger shark CPUE in that region and because samples from this region are relatively abundant across both spatial and temporal scales; i.e.…”
Section: Introductionsupporting
confidence: 81%
“…Such relationship has also been reported in empirical studies (e.g. 37 , 38 ). We chose east coast Australia because of documented reductions in tiger shark CPUE in that region and because samples from this region are relatively abundant across both spatial and temporal scales; i.e.…”
Section: Introductionsupporting
confidence: 81%
“…Even though the Iberian porpoise population was thought to be isolated from other porpoises [ 3 , 68 ], there is evidence of porpoise migration to the Iberian area from southern latitudes (Mauritania or an unknown population occurring between the Portuguese south coast and Mauritania) [ 1 ], emphasizing the need for studies on African porpoise genetics and population parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A sharp decline in genetic diversity detected over the past 25 years indicates that the harbour porpoise population in the western Iberian Peninsula may be small and isolated [ 1 ]. Porpoises inhabiting upwelling areas in the western Iberian Peninsula and Mauritania are genetically differentiated from other populations [ 2 , 3 , 4 ] and a possible subspecies was proposed ( Phocoena phocoena meridionalis ) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genetic studies revealed that the harbour porpoise population in the upwelling areas of the Iberian Peninsula is small and isolated [ 1 , 2 ]. In fact, a new subspecies, Phocoena phocoena meridionalis, has already been proposed to include the so-called Iberian and Mauritanian harbour porpoise groups [ 1 ].…”
Section: Introductionmentioning
confidence: 99%